Piezoelectric device and method for manufacturing piezoelectric device

By adding metal additives such as Mg and Ca to the piezoelectric body layer, the shortcomings in the conversion capacity of existing piezoelectric devices are solved, and more efficient mechanical and electrical energy conversion is achieved.

CN112823432BActive Publication Date: 2025-02-14NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980062655.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-26
Filing Date
2019-09-27
Publication Date
2025-02-14
Estimated Expiration
2039-09-27

AI Technical Summary

Technical Problem

The existing piezoelectric devices are less efficient when efficiently converting vibrations in the thickness direction of the piezoelectric layer into electrical energy or converting electrical energy into mechanical displacement.

Method used

The electromechanical coupling coefficients of the thickness vibration mode are adjusted by adding metal additives that do not exhibit conductivity to the piezoelectric layer of the ZnO-based material having a wurtzite-type crystal structure.

Benefits of technology

The conversion capacity between mechanical energy and electrical energy is improved, and more efficient piezoelectric characteristics are achieved, especially in the vibration mode in the thickness direction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112823432B_ABST
    Figure CN112823432B_ABST
Patent Text Reader

Abstract

A piezoelectric device having a high ability to convert mechanical energy into electrical energy is provided. The piezoelectric device comprises a first electrode layer, a second electrode layer, and a piezoelectric layer disposed between the first electrode layer and the second electrode layer, wherein the piezoelectric layer is formed by adding a non-conductive metal to a ZnO-based material having a wurtzite-type crystal structure, and the square value of the electromechanical coupling coefficient in a thickness vibration mode is greater than 6.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a piezoelectric device and a method for manufacturing the same. Background Art

[0002] Piezoelectric elements that utilize the piezoelectric effect of materials have been used for a long time. The piezoelectric effect refers to the phenomenon that when pressure is applied to a material, polarization proportional to the pressure is obtained. Using the piezoelectric effect, various sensors such as pressure sensors, acceleration sensors, and AE (acoustic emission) sensors that detect elastic waves are produced.

[0003] In recent years, touch panels are used as input interfaces for electronic devices such as smartphones, and piezoelectric elements are widely used in touch panels. The touch panel is integrally formed with the display device of the electronic device, and in order to accurately detect operations performed by fingers, etc., the piezoelectric layer is expected to have high pressure responsiveness. It is also expected to be used in biosensors that detect biological signals such as pulse and respiration, and these applications also require high sensitivity.

[0004] There is known a sintered film of a piezoelectric body obtained by applying and sintering a chemical solution containing a compound having a wurtzite crystal structure to which an alkaline earth metal such as magnesium (Mg) or calcium (Ca) is added using a sol-gel method (for example, see Patent Document 1).

[0005] In addition, a method is known in which a paste obtained by kneading MgO and a varnish is applied on an oriented ZnO film formed by a vapor transport method, and Mg is diffused into the oriented ZnO film by thermal diffusion (for example, see Patent Document 2). In this method, the paste is applied so that the ratio of MgO to the oriented ZnO is 0.05 to 2.0 wt % by weight. Summary of the invention

[0006] Problems to be solved by the invention

[0007] In general, a piezoelectric device has a structure in which a piezoelectric layer is sandwiched between a pair of electrodes. In this case, it is desired to efficiently convert the vibration in the thickness direction of the piezoelectric layer into electrical energy, or conversely, to efficiently convert the given electrical energy into mechanical displacement. The object of the present invention is to provide a piezoelectric device having excellent conversion capability and a method for manufacturing the same.

[0008] Solutions to Solve Problems

[0009] In the present invention, a piezoelectric device having a high ability to convert electrical energy into mechanical energy is realized by adding a metal additive within a predetermined range to the piezoelectric layer.

[0010] Specifically, in a first aspect of the present invention, a piezoelectric device has:

[0011] The first electrode layer,

[0012] a second electrode layer, and

[0013] a piezoelectric layer disposed between the first electrode layer and the second electrode layer,

[0014] The piezoelectric layer is obtained by adding a non-conductive metal to a ZnO-based material having a wurtzite crystal structure, and the square value of the electromechanical coupling coefficient in the thickness vibration mode is 6.5% or more.

[0015] In a second aspect of the present invention, a piezoelectric device includes:

[0016] The first electrode layer,

[0017] a second electrode layer, and

[0018] a piezoelectric layer disposed between the first electrode layer and the second electrode layer,

[0019] The piezoelectric layer is prepared by adding Mg to a ZnO-based material having a wurtzite-type crystal structure, and the content of Mg is 4 to 30 atomic % relative to the total amount of Zn and Mg.

[0020] In a third aspect of the present invention, a piezoelectric device has:

[0021] The first electrode layer,

[0022] a second electrode layer, and

[0023] a piezoelectric layer disposed between the first electrode layer and the second electrode layer,

[0024] The piezoelectric layer is prepared by adding Ca to a ZnO-based material having a wurtzite crystal structure, and the content of Ca is 0.5 atomic % to 5 atomic % based on the total amount of Zn and Ca.

[0025] Effects of the Invention

[0026] Any of the above structures can realize a piezoelectric device with high conversion capability between mechanical energy and electrical energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic diagram of the structure of a piezoelectric device according to an embodiment.

[0028] Figure 2 This is a diagram showing the structure of a sample used in a test to improve piezoelectric properties.

[0029] Figure 3 is a graph showing the frequency dependence of the conversion loss for obtaining the resonant frequency.

[0030] Figure 4AGraph showing the electromechanical coupling coefficient (square value) of a piezoelectric material to which Mg is added, compared with a piezoelectric material to which no metal additive is added.

[0031] Figure 4B The graphs show the half-value width of the X-ray rocking curve and (the square value of) the electromechanical coupling coefficient of the piezoelectric material to which Mg is added, compared with the piezoelectric material to which no metal additive is added.

[0032] Figure 5 The graphs show the half-value width of the X-ray rocking curve and (the square value of) the electromechanical coupling coefficient of the piezoelectric material to which Ca is added, compared with the piezoelectric material to which no metal additive is added.

[0033] Figure 6 A diagram showing a modified example of a piezoelectric device.

[0034] Figure 7 A diagram showing another modified example of the piezoelectric device. DETAILED DESCRIPTION

[0035] Figure 1 1 is a schematic diagram of a piezoelectric device 10A according to an embodiment. The piezoelectric device 10A is used as, for example, a piezoelectric sensor that extracts an electrical signal proportional to a pressure applied from the outside.

[0036] The piezoelectric device 10A has a structure in which a first electrode 12, a piezoelectric layer 13, and a second electrode 14 are sequentially stacked on a substrate 11. In the embodiment, the piezoelectric layer 13 has a wurtzite crystal structure containing a metal additive in a predetermined range.

[0037] Regardless of the type of the substrate 11, a glass substrate, a plastic substrate, a ceramic substrate, or other appropriate material can be used. When a plastic substrate is used, it can be a flexible substrate that can impart bending properties to the piezoelectric device 10A. As the plastic substrate, for example, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), acrylic resin, cycloolefin polymer, polyimide (PI), etc. can be used.

[0038] Among these materials, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), acrylic resin, and cycloolefin polymer are colorless and transparent materials, and are suitable when light transmittance is required for the piezoelectric device 10A. When light transmittance is not required for the piezoelectric device 10A, that is, when it is applied to health management products such as pulse meters and heart rate meters, and vehicle-mounted pressure detection sheets, etc., translucent or opaque plastic materials can be used.

[0039] Any conductive material can be used for the first electrode 12. In applications requiring light transmittance, transparent oxide conductive films such as ITO (indium tin oxide), IZO (indium zinc oxide), IZTO (indium zinc tin oxide), and IGZO (indium gallium zinc oxide) can be used. When transparency is not required, good conductors such as metals such as Au, Pt, Ag, Ti, Al, Mo, Ru, and Cu can be used.

[0040] From the viewpoint of suppressing the unevenness and crystal grain boundaries of the interface between the first electrode 12 and the piezoelectric layer 13, the oxide conductor film can be made an amorphous film. By making it an amorphous film, the unevenness on the surface of the first electrode 12 and the crystal grain boundaries that become the cause of the leakage path can be prevented. In addition, the upper piezoelectric layer 13 is not affected by the crystal orientation of the first electrode 12 and can be grown with good crystal orientation.

[0041] The piezoelectric layer 13 is formed of an inorganic piezoelectric material, for example, having a wurtzite crystal structure. The thickness of the piezoelectric layer 13 is not particularly limited, but is preferably 50 nm or more. This is because if the thickness of the piezoelectric layer 13 is less than 50 nm, it becomes difficult to achieve sufficient piezoelectric characteristics (or polarization proportional to pressure).

[0042] Wurtzite-type crystals have a hexagonal unit lattice and have a polarization vector in a direction parallel to the c-axis. As a wurtzite-type piezoelectric material, zinc oxide (ZnO), zinc sulfide (ZnS), zinc selenide (ZnSe), zinc telluride (ZnTe), aluminum nitride (AlN), gallium nitride (GaN), cadmium selenide (CdSe), cadmium telluride (CdTe), silicon carbide (SiC) can be used, and these components or a combination of two or more of them can be used. In the case of a combination of two or more components, each component can be stacked. Alternatively, these components or a combination of two or more of them can be used as the main component, and other components can be arbitrarily included.

[0043] When ZnO, ZnS, ZnSe, or ZnTe is used as a wurtzite crystal, alkaline earth metals such as Mg, Ca, and Sr, or metals such as vanadium (V), titanium (Ti), zirconium (Zr), and lithium (Li) are added in a predetermined range of proportions. Even if these elements enter the Zn site, they do not exhibit conductivity, but instead increase the value of the electromechanical coupling coefficient.

[0044] When the wurtzite-type crystal material is ZnO, when Mg is added as a metal additive, the doping amount of Mg is preferably 5 to 30 atomic % relative to the total amount of Zn and Mg, and more preferably 10 to 25 atomic %. When Ca is added as an alkaline earth metal, the doping amount of Ca is preferably 0.5 to 5 atomic %, more preferably 0.8 to 2.0 atomic %, and further preferably 0.9 to 1.8 atomic % relative to the total amount of Zn and Ca.

[0045] The second electrode 14 can be formed of any conductive material. When the piezoelectric device 10A requires light transmittance, it can be made of a transparent oxide conductive film such as ITO, IZO, IZTO, IGZO, etc. When light transmittance is not required, it can be made of a metal electrode of a good conductor such as Au, Pt, Ag, Ti, Al, Mo, Ru, Cu, etc.

[0046] Figure 2 The structure diagram of the sample 20 for evaluating the characteristics of the piezoelectric device according to the embodiment. In the sample 20, a Ti film 22 with a thickness of 200 nm is formed by DC sputtering on a quartz glass substrate 21, and a piezoelectric layer 23 of ZnO with a thickness of 6 μm is formed by RF magnetron sputtering while changing the type and amount of dopant added. On the piezoelectric layer 23, a 200 nm thick Au film 24 is deposited as an upper electrode film.

[0047] A plurality of samples 20 with different types and ratios of dopants added to the ZnO piezoelectric layer 23 were prepared under the same size and conditions (excluding the type and amount of dopant added). As a comparative example, a sample of a ZnO layer without dopant added (pure ZnO) was also prepared.

[0048] When Mg is used as a dopant, the content of Mg contained in the piezoelectric layer is changed as described below. When Ca is used as a dopant, the content of Ca in the piezoelectric layer is also changed within a predetermined range.

[0049] When Mg is added, a target of a ZnO sintered body to which MgO is added at a predetermined ratio can be used for sputtering, and a multi-target sputtering device can be used to sputter a ZnO target and a MgO target simultaneously and independently to form a film at a desired doping ratio. When Ca is added, a target of a ZnO sintered body to which CaO is added at a predetermined ratio can be used for sputtering, and a multi-target sputtering device can be used to sputter a ZnO target and a CaO target simultaneously and independently to form a film at a desired doping ratio.

[0050] The composition ratio of the produced film was evaluated using Quantum 2000, which is an ESCA (Electron Spectroscopy for Chemical Analysis) manufactured by ULVAC-PHI Co., Ltd. Specifically, the piezoelectric layer 23 was analyzed by irradiating X-rays from a monochromatic Al Ka ​​source at 15 kV and 30 W. In addition, while etching was performed using Ar ions at an accelerating voltage of 2 kV, a composition analysis was performed at a depth of 200 nm, and the average value was set as the finished film composition ratio (content).

[0051] In the evaluation test, an AC voltage was applied to each sample 20 using a network analyzer (Agilent Technologies) to measure the conversion loss of the piezoelectric layer 23. Specifically, the tip of the probe connected to the terminal of the network analyzer was pressed against the Au film 24 on the upper surface of the sample 20 and an AC voltage was applied. Based on the longitudinal sound waves (ultrasound) generated inside the piezoelectric layer 23, the conversion loss was measured using the network analyzer. By comparing the measured conversion loss with the theoretical curve obtained using Mason's equivalent circuit model, the electromechanical coupling coefficient k of the vibration in the thickness direction of the piezoelectric layer 23 was estimated. t (or its square value k t 2 ).

[0052] In addition, the full width at half maximum (FWHM) of the X-ray rocking curve (XRC) of the piezoelectric layer 23 at each composition ratio is measured. The FWHM value of XRC (hereinafter referred to as "XRC half maximum width") becomes an indicator of the c-axis orientation of the piezoelectric layer 23. The smaller the XRC half maximum width, the better the orientation of the crystal in the c-axis direction.

[0053] Figure 3 The frequency dependence of the conversion loss of a sample having a piezoelectric layer 23 of ZnO (pure ZnO) without doping is shown. The circles are measured values, and the solid line is the theoretical curve of Mason's equivalent circuit model. The dotted line with a very gentle slope near the horizontal axis is the propagation loss.

[0054] The conversion loss is expressed as the ratio of the output frequency power to the input frequency power (dB). The electromechanical coupling coefficient is expressed as the square root of the mechanical energy relative to the supplied electrical energy, so the electromechanical coupling coefficient is related to the conversion loss.

[0055] Figure 3The measured values ​​of the circles are consistent with the calculated values ​​using Mason's equivalent circuit model. The first-order elastic resonance occurs at 303 MHz, and the conversion loss at this time is 4.4 dB. Near 610 MHz, a semi-resonance occurs with a conversion loss as a peak.

[0056] The smaller the conversion loss is, and the farther the resonant frequency is from the semi-resonant frequency, the greater the electromechanical coupling coefficient k in the thickness direction is. t If the resonant frequency is fr and the half-resonant frequency is fa, the square value of the electromechanical coupling coefficient k t 2 For example, as shown below,

[0057] k t 2 =(π / 2)(fr / fa)cot[(π / 2)(fr / fa)].

[0058] The same operation was performed for other samples in which the type and amount of dopants added to ZnO were changed. The resonance frequency at which the conversion loss was minimized and the half-resonance frequency of the peak representing the conversion loss were calculated using a network analyzer, and the square value k of the electromechanical coupling coefficient in the thickness direction of the piezoelectric layer 23 was estimated. t 2 .

[0059] Figure 4A represents k when Mg is added as a dopant t 2 The k value is similar to that of undoped ZnO t 2 k of the piezoelectric layer 23 of undoped ZnO t 2 The value is 5.9%. On the other hand, the doping amount of Mg is set to 10 atomic % relative to the total amount of Zn and Mg, so that k t 2 When the Mg doping amount is 15 atomic % relative to the total amount of Zn and Mg, k t 2 When the doping amount of Mg is 25 atomic % relative to the total amount of Zn and Mg, k t 2 The value is 7.3%.

[0060] About k t 2 The metal dopant also increases the ZnO by about 24-32% compared with the ZnO without addition. It can be seen that by making the addition amount of Mg 5-30 atomic %, the square value k of the electromechanical coupling coefficient in the thickness direction of the piezoelectric layer 23 can be improved. t 2In particular, when the amount of Mg added is 10 to 25 atomic %, the k t 2 The value increased to over 120%.

[0061] Figure 4B Indicates that Figure 4A The XRC half-peak width and k when the Mg content in the piezoelectric layer is changed in a wide range are t 2 When the Mg content in the produced piezoelectric layer (Mg content relative to the total amount of Zn and Mg) is 4.4 atomic % to 20.0 atomic %, k t 2 The value was 7.3% or more, indicating that sufficient resonance was obtained. In addition, the XRC half-peak width was also 3.1° or less, indicating that it was good.

[0062] When the Mg content is 2.5%, the XRC half-peak width is good, but the k t 2 When the Mg doping amount was set to 70 atomic %, no resonance was obtained and k could not be estimated. t 2 value.

[0063] By adding Mg in an appropriate range, the metal dopant has a lower k than ZnO without addition. t 2 The value is increased by nearly 40%, and the XRC half-peak width is also small. Figure 4B From a Mg perspective, the appropriate range of Mg contained in the piezoelectric layer is 4 atomic % to 30 atomic %, and more preferably 4 atomic % to 20 atomic %.

[0064] Figure 5 k is the value when Ca is added as a dopant. t 2 The values ​​and half-peak width of XRC are similar to those of undoped ZnO. t 2 The figure compares the k value and the XRC half-peak width. t 2 The value is 5.9%. On the other hand, by setting the Ca content in the produced piezoelectric layer to 0.9 atomic % relative to the total amount of Zn and Ca, k t 2 When the Ca content is 1.1 atomic % relative to the total amount of Zn and Ca and when the Ca content is 1.7 atomic % relative to the total amount of Zn and Ca, the k t 2If the Ca content is changed to 1.8 atomic % and 3.5 atomic % relative to the total amount of Zn and Ca, k t 2 The values ​​are 6.5 atomic % and 6.3 atomic %, respectively. In this range of the Ca content, the XRC half-peak width is 3.0° or less, which is good.

[0065] On the other hand, if the Ca content is reduced to 0.4 atomic %, k t 2 When the Ca content is increased to 5.1 atomic %, the XRC half-peak width is good, but sufficient resonance cannot be obtained.

[0066] By setting the Ca content in the piezoelectric layer to 0.5 to 5 atomic %, the metal dopant can increase k compared to ZnO without addition. t 2 The value of ZnO can be reduced and the XRC half-peak width can be reduced. More preferably, by making it 0.8 to 3.5 atomic %, k can be reduced compared with ZnO without addition. t 2 The value is increased to about 110% to 118%, and the XRC half-peak width can be reduced. By adding Ca in a predetermined range, both the c-axis orientation and the electromechanical coupling coefficient in the thickness vibration mode are improved.

[0067] Figure 4A , Figure 4B and Figure 5 In the embodiment, the electromechanical coupling coefficient in the thickness vibration mode becomes larger, indicating that the piezoelectric characteristics of the piezoelectric device 10 of the embodiment are improved. By adding a metal material that does not exhibit conductivity in the zinc oxide sputtered film having a wurtzite crystal structure, the square value of the electromechanical coupling coefficient in the thickness vibration mode (k t 2 ) is 6.3% or more, more preferably 6.5% or more. t 2 ) is increased by 1 to 25%. In addition, the c-axis orientation can be improved.

[0068] <Modification>

[0069] Figure 6 Schematic diagram of a piezoelectric device 10B as a modified example. The piezoelectric device 10B has an orientation control layer 17 under the piezoelectric layer 13. The orientation control layer 17 is an amorphous layer for improving the c-axis orientation of the piezoelectric layer 13, and has a thickness of 3 nm to 100 nm.

[0070] The orientation control layer 17 is formed by an inorganic substance, an organic substance, or a mixture of an inorganic substance and an organic substance. As an inorganic substance, silicon oxide (SiOx), silicon nitride (SiN), aluminum nitride (AlN), aluminum oxide (Al2O3), gallium nitride (GaN), gallium oxide (Ga2O3), etc. can be used. Alternatively, ZnO (zinc oxide with aluminum / silicon added; hereinafter referred to as "SAZO") added with Al2O3 and SiOx, or GaN, AlN, ZnO, etc. added with at least one of Al2O3, Ga2O3, SiOx, and SiN can be used.

[0071] As organic matter, organic matter such as acrylic resin, urethane resin, melamine resin, alkyd resin, siloxane polymer can be cited. As organic matter, it is particularly preferred to use a thermosetting resin formed by a mixture of melamine resin, alkyd resin and organosilane condensate. The above materials can be used to form an amorphous film by vacuum evaporation, sputtering, ion plating, coating, etc. The orientation control layer can be 1 layer, or it can form a stack of 2 layers or more. When forming a stack, a stack of an inorganic thin film and an organic thin film can be formed.

[0072] The amorphous orientation control layer 17 using these materials has excellent surface smoothness and can orient the c-axis of the upper wurtzite crystal layer in the vertical direction (stacking direction). In addition, it has high gas barrier properties. When a plastic substrate is used as the substrate 11, the influence of the gas originating from the plastic layer during film formation can be reduced. In particular, when the orientation control layer 17 is formed of a thermosetting resin, it is amorphous and has high smoothness. When melamine resin is used for the orientation control layer 17, due to the three-dimensional cross-linked structure, it has high density and high barrier properties.

[0073] The orientation control layer 17 does not necessarily need to be 100% amorphous, and may have a non-amorphous region within a range that can improve the c-axis orientation of the piezoelectric layer 13. In the region of the orientation control layer 17, if the proportion of the region formed by the amorphous component is preferably 90% or more, more preferably 95% or more, a sufficient c-axis orientation control effect can be obtained.

[0074] The piezoelectric layer 13 formed on the orientation control layer 17 is formed of a wurtzite-type crystalline material to which a metal additive is added. The metal additive is a metal that does not exhibit conductivity when added. When ZnO, ZnS, ZnSe, ZnTe, etc. are used as wurtzite-type crystals, alkaline earth metals such as Mg, Ca, Sr, or metals such as vanadium (V), titanium (Ti), zirconium (Zr), and lithium (Li) are added in a ratio within a predetermined range.

[0075] When Mg is added as a dopant in zinc oxide, the content of Mg in the film is 4 to 30 atomic % relative to the total amount of Zn and Mg, and more preferably 4 to 20 atomic %. When Ca is used as a dopant in zinc oxide, the content of Ca in the film is 0.5 to 5 atomic % relative to the total amount of Zn and Ca, and more preferably 0.8 to 3.5 atomic %.

[0076] By doping Mg or Ca in a ratio within this range, the electromechanical coupling coefficient in the thickness vibration mode can be improved compared with undoped zinc oxide having a wurtzite crystal structure.

[0077] Furthermore, even if metals other than Mg and Ca are added, such as V, Ti, Zr, Sr, Li, etc., the piezoelectric properties of the zinc oxide material having a wurtzite crystal structure in the film thickness direction can be improved. In addition, a mixture of these metals may be added.

[0078] Furthermore, by inserting the amorphous orientation control layer 17 into the base, the c-axis orientation of the piezoelectric layer 13 is improved, and the piezoelectric characteristics of the piezoelectric device 10B are further improved.

[0079] The substrate 11 may be made of any material, such as a glass substrate, a plastic substrate, or a ceramic substrate. The first electrode 12 may be made of any material as long as it is a conductive film. When light transmittance is required according to the application of the device, a transparent conductive film may be used, and when light transmittance is not required, a metal electrode may be used. When a transparent electrode is used, the first electrode 12 may be formed of an amorphous oxide conductor.

[0080] Figure 7 1 is a schematic diagram of a piezoelectric device 10C as another modified example. In the piezoelectric device 10C, an adhesive layer 16 is disposed at the interface between the piezoelectric layer 13 and the second electrode 14 .

[0081] The piezoelectric layer 13 is formed of a wurtzite-type crystalline material to which a metal additive is added. The metal additive is a metal that does not exhibit conductivity when added. When ZnO, ZnS, ZnSe, ZnTe, etc. are used as the wurtzite-type crystal, an alkaline earth metal such as Mg, Ca, Sr, or a metal such as vanadium (V), titanium (Ti), zirconium (Zr), lithium (Li) is added in a ratio within a predetermined range.

[0082] When Mg is added as a dopant in zinc oxide, the content of Mg in the film is 4 to 30 atomic%, more preferably 4 to 20 atomic%, relative to the total amount of Zn and Mg. When Ca is added as a dopant in zinc oxide, the addition ratio of Ca is 0.5 to 5 atomic%, more preferably 0.8 to 3.0 atomic%, relative to the total amount of Zn and Ca. By doping Mg or Ca in a ratio within this range, the electromechanical coupling coefficient in the thickness vibration mode can be improved compared to undoped zinc oxide of a wurtzite crystal structure.

[0083] The adhesive layer 16 suppresses leakage paths caused by cracks and pinholes generated in the piezoelectric layer 13. If a metal grain boundary or a protrusion exists at the interface between the piezoelectric layer 13 and the first electrode 12 or the interface between the piezoelectric layer 13 and the second electrode 14, a leakage path is formed between the electrodes due to cracks, etc., and polarization disappears. By inserting the adhesive layer 16, the formation of the leakage path is suppressed, and the piezoelectric characteristics of the piezoelectric layer 13 are well maintained.

[0084] The method for manufacturing the piezoelectric device 10C is as follows. As the first part, a first electrode 12 is formed on a substrate 11, and a piezoelectric layer 13 to which a predetermined dopant is added at a predetermined ratio is formed on the first electrode 12. On the other hand, as the second part, a second electrode 14 is formed on a substrate 18. Regardless of the type of the substrate 18, a plastic substrate can be used as an example. The piezoelectric layer 13 and the second electrode 14 are placed opposite to each other, and the first part and the second part are bonded together using an adhesive layer 16, thereby completing the stacked structure of the piezoelectric device 10C.

[0085] The piezoelectric device 10C has a large electromechanical coupling coefficient in the thickness vibration mode, suppresses the leakage path between electrodes, and has excellent piezoelectric characteristics.

[0086] The piezoelectric device 10 of the present invention can be used not only in devices using the piezoelectric effect, such as a touch panel force sensor, a pressure sensor, an acceleration sensor, and an acoustic emission sensor, but can also be used in speakers, converters, high-frequency filter devices, etc., using the inverse piezoelectric effect. In this case, the conversion efficiency from electrical energy to mechanical energy is high, and a large displacement in the thickness direction can be obtained.

[0087] The configuration of the piezoelectric device 10 is not limited to the above-described embodiment. Figure 6 and Figure 7 In the structure of , the second electrode 14 can be formed by a transparent conductive film. Figure 6 and Figure 7The structure of the present invention is combined with that of the present invention, an orientation control layer 17 is inserted between the piezoelectric layer 13 and the first electrode 12, and the piezoelectric layer 13 and the second electrode 14 are bonded together by an adhesive layer 16. In this case, as the first part, the first electrode 12 is formed on the substrate 11, the orientation control layer 17 is formed on the first electrode 12, and the piezoelectric layer 13 to which a predetermined dopant is added at a predetermined ratio is formed on the orientation control layer 17. As the second part, the second electrode 14 is formed on the substrate 18, the piezoelectric layer 13 and the second electrode 14 are opposed to each other, and bonded together by an adhesive layer 16.

[0088] In either case, the piezoelectric layer 13 has good piezoelectric characteristics in the thickness direction and can achieve high conversion efficiency.

[0089] When ZnO is used as the main component of the piezoelectric layer 13 , a mixture of Mg and Ca may be added.

[0090] This application claims priority based on Japanese Patent Application No. 2018-185549 filed on September 28, 2018 and Japanese Patent Application No. 2019-176135 filed on September 26, 2019, and incorporates the entire contents of these Japanese Patent Applications.

[0091] Explanation of symbols

[0092] 10, 10A~10C Piezoelectric devices

[0093] 11. Substrate

[0094] 12. 1st electrode (1st electrode layer)

[0095] 13 Piezoelectric layer

[0096] 14. Second electrode (second electrode layer)

[0097] 16 Adhesive layer

[0098] Prior art literature

[0099] Patent Literature

[0100] Patent Document 1: (Japan) Patent No. 6273691

[0101] Patent Document 2: (Japanese) Patent Publication No. 8-310813

Claims

1. A piezoelectric device, characterized in that: have: The first electrode layer, a second electrode layer, and a piezoelectric layer disposed between the first electrode layer and the second electrode layer, The piezoelectric layer is made by adding Mg to a ZnO-based material having a wurtzite-type crystal structure, and the square value of the electromechanical coupling coefficient in the thickness vibration mode is 7.8% or more. The thickness of the piezoelectric layer is greater than 50 nm. The content of Mg in the piezoelectric layer is 6.4 atomic % or 14.2 atomic % to 20 atomic %.

2. A piezoelectric device, characterized in that: have: The first electrode layer, a second electrode layer, and a piezoelectric layer disposed between the first electrode layer and the second electrode layer, The piezoelectric layer is formed by adding Ca to a ZnO material having a wurtzite crystal structure, the square value of the electromechanical coupling coefficient in the thickness vibration mode is 6.5% to 6.9%, and the content of Ca is 0.5 atomic % to 5 atomic % relative to the total amount of Zn and Ca. The piezoelectric layer has a thickness of 50 nm or more.

3. The piezoelectric device according to claim 1 or 2, characterized in that: The piezoelectric layer has an X-ray rocking curve with a full width at half maximum of 5° or less.

4. The piezoelectric device according to claim 1 or 2, characterized in that: The first electrode layer is formed on a substrate of quartz or glass.

5. The piezoelectric device according to claim 1 or 2, characterized in that: The piezoelectric device is formed on a plastic substrate.

6. The piezoelectric device according to claim 5, characterized in that: The piezoelectric device is provided with an amorphous orientation control layer between the piezoelectric layer and the plastic substrate, and the amorphous orientation control layer is formed by an inorganic substance selected from the group consisting of silicon oxide, silicon nitride, aluminum nitride, aluminum oxide, gallium nitride, gallium oxide, and zinc oxide added with aluminum / silicon; an organic substance selected from the group consisting of acrylic resin, urethane resin, melamine resin, alkyd resin, and siloxane polymer; or a mixture of the inorganic substance and the organic substance.

7. The piezoelectric device according to claim 1, 2 or 6, characterized in that: An adhesive layer is arranged between the piezoelectric layer and the second electrode layer.

8. The piezoelectric device according to claim 7, characterized in that: A second substrate is disposed on the second electrode layer.

9. A method for manufacturing a piezoelectric device, characterized in that: On the first electrode, a piezoelectric layer of a ZnO-based material having a wurtzite-type crystal structure is formed by sputtering. A second electrode is arranged on the piezoelectric layer along the stacking direction. In the sputtering, Mg is added to the inside of the piezoelectric layer so that the square value of the electromechanical coupling coefficient in the thickness vibration mode of the piezoelectric layer becomes 7.8% or more. The thickness of the piezoelectric layer is greater than 50 nm. The content of Mg in the piezoelectric layer is 6.4 atomic % or 14.2 atomic % to 20 atomic %.

10. A method for manufacturing a piezoelectric device, characterized in that: On the first electrode, a piezoelectric layer made of a ZnO material having a wurtzite crystal structure and to which Ca is added is formed by sputtering. A second electrode is arranged on the piezoelectric layer along the stacking direction. The content of Ca in the piezoelectric layer formed by the sputtering is 0.5 atomic % to 5 atomic % relative to the total amount of Zn and Ca, and the square value of the electromechanical coupling coefficient in the thickness vibration mode is 6.5% to 6.9%. The piezoelectric layer has a thickness of 50 nm or more.

11. The method for manufacturing a piezoelectric device according to claim 9 or 10, characterized in that: The method further includes bonding the piezoelectric layer and the second electrode together using an adhesive layer.

Citation Information

Patent Citations

  • Performance confirmation method of substrate treatment device

    JP2018185549A

  • Substrate processing apparatus, control system, and manufacturing method for semiconductor device

    JP2019176135A

  • Electronic device and method of fabricating the same

    CN1665043A

  • Orientated zno based piezoelectric material and its production

    JP1996310813A

  • Piezoelectric device and manufacturing method of the same

    JP2018170503A